Effects of probiotic bacteria, isoflavones and simvastatin on lipid profile and atherosclerosis in cholesterol-fed rabbits: a randomized double-blind study - Cavallini, Daniela Cardoso Umbelino [UNESP]; Bedani, Raquel [UNESP]; Bomdespacho, Laura Q. [UNESP]; Vendramini, Regina Célia [UNESP]; Rossi, Elizeu Antonio [UNESP] (Biomed Central Ltd., 2009)
Background: Much attention has been drawn to different alternative strategies for cardiovascular disease prevention. Objective: The aim of the present study was to observe and compare the effects of Enterococcus faecium CRL183 (probiotic microorganism), an isoflavones mixture and simvastatin (drug used to treat hypercholesterolemia) on lipid parameters and atherosclerosis development in rabbits with induced hypercholesterolemia.Methods: The animals were randomly allocated to 5 experimental groups (n = 6) for 60 days: control (C) that did not consume cholesterol, hypercholesterolemic (H) that consumed an atherogenic diet (1.0% cholesterol wt/wt), hypercholesterolemic plus E. faecium (HE), hypercholesterolemic plus isoflavone (HI) and hypercholesterolemic plus simvastatin (HS). Total and HDL-cholesterol and triglycerides were determined by enzymatic methods; non-HDL-C was calculated by subtracting HDL-C from total cholesterol; and atherosclerosis was presented as the percentage of lesion area, relative to the total area from the aorta segment analyzed.Results: Simvastatin significantly reduced the tot cholesterol (16%) and non-HDL-C level (17%) and increased the HDL-C (98%), compared to group H. E. faecium raised the HDL-C level by 43.3% (P < 0.05). Isoflavone decreased the total cholesterol and non-HDL-C concentrations (9%), but this effect was not statistically significant. At the end of the treatments, groups HE and HS had significantly lower levels of triglycerides in relation to H and HI. The atherosclerotic lesion area in the aortic arch was not different between groups. The extent of atherosclerosis in the thoracic and abdominal aorta was reduced in the groups HI and HS by 22.7% and 26.7% respectively, but this effect was not significant (P > 0.05).Conclusion: The results indicated that probiotic microorganism E. faecium CRL 183 could be used to improve the lipid profile as an alternative or an adjuvant for drug therapy. The effectiveness of simvastatin in the management of blood lipid was confirmed. There were no effects of soy isoflavones, E. faecium and simvastatin on atherosclerosis development.